FACTORS INFLUENCING THE PRACTICE OF BREAST SELF EXAMINATION AMONG YOUNG WOMEN IN IBADAN NORTH WEST LOCAL GOVERNMENT AREA, OYO STATE (2014)
Breast Cancer (BC) is the commonest cancer and a major cause of death among women worldwide. Breast Self Examination (BSE) is a screening technique for its early detection. However, not much is known about the adoption of BSE and the factors affecting it among Nigerian women. The objective of the study was to assess the level of knowledge, frequency and factors influencing the practice of BSE among young women in Ibadan North West Local Government Area, Oyo State. The study was a descriptive cross-sectional survey. A four-stage random sampling technique was utilised for the study. The first stage was the selection of the LGA, second stage was the selection of wards, the third stage was the selection of households from the central point of the community utilizing the systematic sampling technique. Finally a respondent was selected from each household using a simple random sampling technique (balloting) among those eligible to participate in the study. A total of 370 respondents aged between 15 and 29 years participated in the study. A semi-structured questionnaire which included a 7-point knowledge scale of BSE was used to collect information on socio-demographic characteristics, perceived susceptibility to BC and practice of BSE (knowledge score of ≤ 3 was rated as poor and > 3 rated as good knowledge). Eight Focus Group Discussions (FGDs) (2 in each of EleyeleOja, Benjamin, Olopomewa and Eleyele roundabout) were conducted. Quantitative data were analysed using descriptive statistics and Chi square test while the FGD results were analysed using thematic approach. Respondents’ mean age was 22.5 ±3.9 years, 52.7% were students and 74.3% were single. Those who had primary, secondary and tertiary education were 7.3%, 49.5% and 43.2% respectively. Majority(52.2%)had heard about BSE and mean knowledge score of BSE was 2.6 ± 1.4. Only 15.4% of the respondents had good knowledge of BSE and about a third (32.2%) reportedly practiced BSE as at the time of the study. Reported frequency of BSE was monthly (14.3%), weekly (8.6%), daily (7.3%) and yearly (1.9%). Respondents with tertiary education (55.8%) were more likely to practise BSE compared to those with secondary (36.1%) and primary (5.0%) respectively (p<0.05). Only 13.2% of respondents perceived themselves to be susceptible to BC. The perceived factors which hindered practice of BSE included lack of knowledge (48.6%), perception of non-vulnerability to breast cancer (19.2%) and lack of time (17.8%). The FGD participants unanimously agreed that low practice of BSE among the women was due to perception of non-vulnerability to BC. Poor knowledge of breast self examination, perception of non vulnerability to breast cancer and poor practice of breast self examination were common among the respondents. A scale up of education of women is recommended for promoting adoption of Breast Self Examination.